Konkurencyjność gmin wiejskich województwa zachodniopomorskiego pod względem jakości produktu turystycznego - Bąk, Iwona (Competitiveness of Tourist Product in the Country Communes of Westpomeranian Voivodeship, 2006)
The aim of the article is a statistical analysis of a tourist product in communes of Westpomeranian voivodeship with special regard to country communes and also test of creation of analysed communes with regard to attractiveness of a tourist product. Special attention is paid in this paper to attractiveness of natural environment, because it is the basic element of tourist values quality. For the classification of communes the pattern of development by Hellwig was used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 63-68